Handbook of dermatology : a practical manual - Mann, Margaret W. (Wiley-Blackwell, 2009)
Because dermatology is a complex visual specialty that mixes medical and surgical approaches to management, trainees need fast access to a wide range of material. This concise new reference uses tables, algorithms, protocols, guidelines, and staging and scoring systems to present succinct guidance on best-practice patient care. Structured around three components -- medical, surgical, and pharmacological -- the book consolidates the core Board exam information residents most often look up. Handbook of Dermatology: A Practical Manual was road-tested as it was developed to ensure usefulness for.